Germáni: Dějiny a zrod rasové teorie - Linda Ambrožová (AntropoWebzin, 2008)
The main aim of this paper was to catch the most important events of one thousand years lasting time period of German history and to provide a  summary of German evolution since the end of the wandering of nations for a purpose of understanding the circumstances under which the German racist ideology was established. On the bases of the selected sources could be assumed that the expansion of polygenetism, next the progressive secularization of Western thought and the progress of natural sciences played the significant role. It was a Darwin’s theory as well that contributed significantly to enforcement of racist concept based on biological features. The German racist ideology originated on the bases of those sources: so called ideology of “two races” that was retrieved during the French revolution; fascination by India and Indo-European concept (that connected together Aryans and Germans in eighteen century); German nationalism and Romanism and the ideology about superiority of Germans. Also the work of Arthur Gobineau played the important role for transformation of the philological-historical concept of Aryan race into the ideology of Aryans as the members of biological superior race.